A brief report of real-world evidence development (RWD/RWE) in 2021: United States, Russia, and the Eurasian Economic Union (EAEU) - A. S. Kolbin; D. Yu. Belousov (Реальная клиническая практика: данные и доказательства)
The article provides a brief overview of the main trends in the development of real-world data and real-world evidence (RWD/RWE) paradigm in the United States, Russia, and the Eurasian Economic Union (EAEU) in 2021. The review is compiled in calendar sequence. First, events in the United States are presented, sourced from the information resource, "The Evidence Base". Following this, data for the Russian Federation and the EAEU are collected and stored on the "myRWD — Real Clinical Practice" Facebook page, and in the journal "Real-World Data & Evidence". The information is summarized and a complete picture of the development of real clinical practice and its evidence in the indicated countries is given.